Strategi Guru Agama dalam Menerapkan Proyek Penguatan Profil Pelajar Pancasila Dengan Tema “Bulliying” pada Siswa di SMAN 1 Kota Bengkulu - Febrianto, Redo (UIN Fatmawati Sukarno Bengkulu, 2021)
School is a place to get general education and religious education at elementary and secondary levels. Therefore, this thesis aims to determine the Strategy of Religious Teachers in Implementing the Pancasila Student Profile Strengthening Project with the Theme of